Conceptualizing Childhood in the Qur’an through a Tafsir and Linguistic Analysis of Walad, Ṣibyān, Ṭifl, and Ghulām with Educational Implications - Heru Saiful Anwar; Fathma Zahara Sholeha; Safiruddin Al Baqi (Educan, 2026)
This study examines the concept of childhood in the Qur’an through a tafsir and Arabic linguistic analysis of four key terminologies: walad, ṭifl, ṣibyān, and ghulām. Rather than employing a single, generic notion of “child,” the Qur’an uses these terms to represent distinct stages of development, relational contexts, and moral capacities. Using a qualitative literature-based method, this study analyzes selected Qur’anic verses and classical as well as contemporary Qur’anic interpretations to explore the semantic nuances and contextual usage of each term. The findings reveal that walad emphasizes familial relations and parental moral responsibility, ṭifl denotes early biological dependence and limited social awareness, ṣibyān reflects the emergence of moral and spiritual potential in early childhood, and ghulām represents a transitional phase toward independence and responsibility. Collectively, these terminologies form a developmental continuum that underscores the Qur’an’s dynamic and layered conception of childhood. The study further argues that this terminological differentiation provides an important conceptual foundation for contemporary Islamic education, calling for a gradual, contextual, and developmentally sensitive educational approach. By integrating Qur’anic semantics with educational reflection, this study contributes to a deeper understanding of child-centered education within an Islamic framework.